2012
DOI: 10.1530/eje-11-0693
|View full text |Cite
|
Sign up to set email alerts
|

Serum inhibin pro-αC is a tumor marker for adrenocortical carcinomas

Abstract: Objective: The insufficient diagnostic accuracy for differentiation between benign and malignant adrenocortical disease and lack of sensitive markers reflecting tumor load emphasize the need for novel biomarkers for diagnosis and follow-up of adrenocortical carcinoma (ACC). Design: Since the inhibin a-subunit is expressed within the adrenal cortex, the role of serum inhibin pro-aC as a tumor marker for ACC was studied in patients. Methods: Regulation of adrenal pro-aC secretion was investigated by adrenocortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
2
15
1
Order By: Relevance
“…Primary cultures of adrenocortical cells secreted activin A, inhibin B, and inhibin pro-␣C, whereas inhibin A levels were undetectable. Adrenocortical production of inhibin pro-␣C and to a lesser extent inhibin B is compatible with the reports that these peptides can be elevated in serum of patients with adrenocortical tumors (16,22). The finding that activin A and inhibin pro-␣C were amply produced without concomitant secretion of inhibin A indicates the different cell types in which these subunits are expressed, e.g., zona glomerulosa for the inhibin ␤A-subunit and reticularis for the ␣-subunit (26,33).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Primary cultures of adrenocortical cells secreted activin A, inhibin B, and inhibin pro-␣C, whereas inhibin A levels were undetectable. Adrenocortical production of inhibin pro-␣C and to a lesser extent inhibin B is compatible with the reports that these peptides can be elevated in serum of patients with adrenocortical tumors (16,22). The finding that activin A and inhibin pro-␣C were amply produced without concomitant secretion of inhibin A indicates the different cell types in which these subunits are expressed, e.g., zona glomerulosa for the inhibin ␤A-subunit and reticularis for the ␣-subunit (26,33).…”
Section: Discussionsupporting
confidence: 88%
“…The role of its antagonist inhibin in adrenocortical physiology is even more obscure, since it has failed to show consistent effects on steroidogenesis (33,36,39). On the other hand, the inhibin ␣-subunit has been implicated in adrenocortical tumor formation in murine models (14,24) and can function as a tumor marker in patients (16).…”
mentioning
confidence: 99%
“…In contrast, in vivo studies have revealed increased levels of the inhibin α-subunit in serum of patients with ACC [21], [31], [32]. These findings are likely to be a consequence of the wide variation in tumor INHA expression levels, in the current study over a 1000-fold.…”
Section: Discussioncontrasting
confidence: 62%
“…Furthermore, comparative genomic hybridization analyses of human ACCs described sporadic chromosomal loss of the INHA region at 2q33-36, with a predominance in childhood tumors [33], [34], [35]. On the other hand, the inhibin α-subunit was previously shown to be overexpressed in pediatric ACCs [21].…”
Section: Discussionmentioning
confidence: 99%
“…The proteins of the first three genes are key steroidogenic enzymes of cortisol production, whereas the inhibin ␣-subunit is presumably involved in adrenocortical cell proliferation and can serve as a tumor marker for ACC (30,31). We measured the induction of the above-mentioned genes by ACTH in a variety of adrenocortical primary cultures as an indicator of ACTH responsiveness.…”
Section: Mrap Mrap2 Mc2r and Acth Responsivenessmentioning
confidence: 99%